MEDICINAL PROPERTIES - LISSACHATINA FULICA - Safarova Zakiya Teshayevna; Asadova Nilufar Yorkinovna (Scholar Express Journal, 2022)
The article provides information about the widespread use of natural remedies by mankind, the medicinal properties of soft-bodied mollusks and their use in cosmetology
Keywords: Mollusca; Achatines; soft-bodied; gastropods